The Impact of the Digital Economy on E-Commerce Development - Wanrou Jiang (Journal of World Economy, 2022)
The establishment of Taobao in 2003, to Pinduoduo in 2015, shows the rapid development of the digital economy and people’s increased needs. Taobao was launched as a C2C (consumer-to-consumer) marketplace, a website for the whole world. Both overseas and Chinese users can buy directly from this site. In just two years it has taken over most of the Chinese market and with it has reduced economic poverty in other parts of China. The initial success of Taobao laid the foundations for e-commerce in China, with the British magazine The Economist calling it “China’s biggest online bazaar”. Since then, many e-commerce companies have tried to replicate Taobao’s success, but unfortunately many have failed, but Pinduoduo has managed to rival Taobao. The biggest advantage of C2B (consumer to business) is that it eliminates many intermediate steps and maximizes benefits. This means that Pinduoduo uses a collocation model to gather a large number of users, who then work together to place orders with the company at a group price, which greatly reduces the cost of sales.